INTERNATIONAL IMAGE OF CENTRAL ASIA AND UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The article examines the international image of Central Asia and Uzbekistan in the context of contemporary transformations in world politics and regional development. Particular attention is paid to the fact that in the twenty-first century the power of a state is determined not only by its military, economic or resource potential, but also by its reputation, foreign-policy legitimacy, investment attractiveness, cultural influence and diplomatic reliability. The paper analyzes the changing international perception of Central Asia: from earlier stereotypes associated with closed political systems, raw-material dependence, transport isolation and geopolitical rivalry among major powers, toward a new image of the region as an important transport and logistics hub, a source of energy and raw materials, a space of demographic growth, multi-vector diplomacy and regional integration.